Graph-based version control for asynchronous BIM collaboration. (August 2022) - Esser, Sebastian; Vilgertshofer, Simon; Borrmann, André
Abstract: Collaboration and communication are two essential aspects of Building Information Modeling (BIM). Current practice and international standards implement BIM collaboration on the basis of domain model federation where loosely coupled models are managed as separated files and coordinated in a mostly manual fashion. The concept has severe limitations regarding concurrency and version control, as the granularity of change tracking remains on the level of complete files and does not reach individual model objects. Due to this lack of change traceability, high manual effort for the subsequent coordination across the domains is generated. These limitations can be overcome by implementing modern approaches of digital collaboration based on object-level synchronization, widely denoted as BIM level 3. This paper presents a sound methodological basis for object-based version control by (1) representing the object networks of BIM models as formal property graph structures and (2) describing changes of the model by graph transformations. Consequently, modifications can be transmitted as graph transformation rules which are subsequently integrated on the receiving side, thus achieving object-level synchronization. The paper provides the underlying theory of describing model changes by means of graph transformations and demonstrates its benefits using the example of domain models implementing the Industry Foundation Classes (IFC) as their underlying data model.